Factors Affecting Blood Glucose in Type 2 Diabetes Mellitus Patients: The Role of Diet, Physical Activity, and Medication Adherence in The Prolanis Program at Denkesyah Clinic, Madiun, East Java - Sad Omega Kencanawaty; Nurwijayanti; Novita Ana Anggraini (Ficco Public Health Journal, 2025)
Background: Diabetes Mellitus (DM) is a chronic disease that requires continuous management. Blood glucose control is strongly influenced by lifestyle factors, including diet, physical activity, and medication adherence. This study aimed to analyze the effect of diet, physical activity, and medication adherence on blood glucose levels among diabetes mellitus patients participating in the Prolanis program at Denkesyah Clinic, Madiun, East Java. Methods: A quantitative cross-sectional study at Denkesyah Clinic Madiun, from June to July 2025. A total of 69 respondents were purposively selected from 224 Prolanis participants. Data were collected using structured questionnaires and fasting blood glucose measurements. Multiple linear regression analysis was applied to determine the associations between variables. Results: Diet was categorized as good (37.7%), physical activity as moderate (34.8%), medication adherence as high (43.5%), and blood glucose as abnormal (50.7%). Regression analysis revealed significant associations between diet (p=0.030), physical activity (p=0.001), and medication adherence (p=0.000) with blood glucose. Medication adherence was the most influential factor (highest Beta). Conclusions: Diet, physical activity, and medication adherence significantly affect blood glucose control, with adherence to medication being the strongest determinant. Strengthening education and adherence monitoring within the Prolanis program is essential for achieving optimal glycemic control.